A THEOLOGICAL AND LITERARY FRAMEWORK OF THE PSALMS: Exploring Its Unified Structure - Lie, Sioe; Putrawan, Bobby Kurnia; Sutrisno, Sutrisno (Sekolah Tinggi Teologi Moriah, 2024)
Interpreters often view the book of Psalms as a collection of liturgical songs used in temple worship. While this perspective is not incorrect, it has led to a tendency to interpret each psalm in isolation, without considering its relationship to other psalms in the book. This research introduces a broader perspective, suggesting that the book of Psalms is not merely a compilation of individual songs but rather an intentionally arranged collection with a unified structural pattern culminating in Psalm 150. In this sense, Psalms 1 to 150 can be seen as a series of milestones leading to this peak. To fully grasp the message of a particular psalm, it is necessary not only to interpret it individually but also to examine its placement within the overall structure of the book and its function within the larger sequence arranged by the editor.